Examining the risk reduction strategies of actors in online criminal markets. - Holt, Thomas J.; Smirnova, Olga; Chua, Yi Ting; Copes, Heith (Global Crime, 2015)
Research examining offender risk reduction strategies within illicit markets focus primarily on those operating in the real world for drugs and stolen goods. Few have considered the strategies that may be used by individuals in virtual illicit markets that are hidden from public view. This study addresses this gap through a grounded theory analysis of posts from 10 Russian and three English language web forums selling stolen data to engage in identity theft and fraud. The findings indicate that buyers employ multiple strategies to reduce their risk of loss from unreliable vendors, along with resources provided by forum administrators to manage relationships between participants. The implications of this study for law enforcement and offender decision-making research are also discussed.